ANALISIS PENGARUH PERSEPSI TEKNOLOGI DAN PERSEPSI RISIKO TERHADAP KEPERCAYAAN PENGGUNA M-BANKING - Adhi Prakosa (Jurnal Manajemen, 2019)
M-banking is a banking service that makes it possible to conduct banking transactions via mobile phones with an internet connection. Through m-banking, banking transactions become easier and simpler. One measure of the success of a bank is needed based on trust. Trust in m-banking depends on the perception of technology and the perceived risk of using the m-banking. We propose that 1) technology perceptions influence significantly on trust 2) risk perceptions significant to trust 3) technology perceptions and risk perceptions simultaneously influence trust and 4) technology perceptions have a significant influence on risk perceptions. The population in this study was that m-banking users with samples of 71 respondents were obtained through questionnaires. The data analysis technique used in this study is the t test and F test. The test results show that each hypothesis is accepted with a significance of less than 0.05 which means that 1) the perception of technology influences the significance of trust 2) the perception of risk influences the significance of trust 3) the perception of technological technology has a significant influence on perceived risk. Adjusted R Square 11% shows that there are still many factors beyond the perception of technology and perceptions of risk that can explain trust.